Argentina: "Pollinator - friendly flower strips with native species from Pampa grassland - Stancanelli, Santiago (2024)
According to Instituto de Floricultura ,Global biodiversity is in decline, driven primarily by human activities such as agricultural intensification and expanding urban development.